Feasibility Study of Wind-Diesel Stand-Alone System for a Small Village in India - Badruddin, Irfan Anjum (International Journal of Integrated Engineering, 2020)
The finite resources of energy like coal, oil, natural gas etc are depleting day by day. On the other hand man is exploring new ways of utilizing energy and thus total energy requirement of the world is increasing continuously. With the present rate of utilization, the underground deposits of coal, oil and natural gas are expected to last for approximately, 100 years, 50 years and 50 years respectively. To cope up with this problem, concerted efforts to generate renewable energy as an alternate source is increasing rapidly with the passage of time. Among the available renewable resources, solar energy and wind energy are the prime candidates getting attention around the world for power generation. Wind energy is a very good option for power generation but suffers due to variation in wind speed and thus the power contained in the wind, when considered on yearly basis. There are various methods to suppress this drawback of wind energy. One such option is the wind-diesel system. This paper highlights, an analysis of the wind-diesel stand-alone system to meet the complete energy requirement such as house lighting, water pumping, laboratory operations for processing the salt, sealing machine operation etc., of a remotely located community in India.